Multiple myeloma and light-chain amyloidosis: a rare presentation - carmenza Liliana Sandoval; Bernarda Jinneth Acosta; Oscar Contreras; Jorge Vargas (Case Reports)
Introduction: Primary systemic amyloidosis is part of the spectrum of plasma cell neoplasms, in which immunoglobulin light chains are deposited in multiple organs. However, myopathic involvement along with respiratory failure and associated multiple myeloma is a rare condition. Clinical case: This paper presents the case of a patient with systemic light chain amyloidosis who was admitted due to myopathy with respiratory failure and adynamic ileus that required intensive care. Infiltration in skin and digestive tract was confirmed by histology. The patient presented with concomitant multiple myeloma with lytic bone lesions and myeloma kidney. The patient responded well to the CyBorD scheme (cyclophosphamide, bortezomib, dexamethasone), renal function was recovered and skin lesions decreased. However, gastrointestinal and myopathic involvement was difficult to manage, requiring ventilatory support and parenteral nutrition. Discussion: Clinicians may oversee this pathology, leading to advanced stages of the disease. Currently, new chemotherapy agents and autologous transplantation may increase the survival of these patients. Conclusion: AL amyloidosis has a wide spectrum of manifestations and should be considered in differentials to reach an early diagnosis and make it treatable.